1985
DOI: 10.1172/jci112240
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-mediated reduction of whole body protein breakdown. Dose-response effects on leucine metabolism in postabsorptive men.

Abstract: In vivo effects of insulin on plasma leucine and alanine kinetics were determined in healthy postabsorptive young men (n = 5) Leucine oxidation estimated from the GC-enrichment of expired CO2 and plasma leucine (12±1 ,umolkg. hr-) and from the '3C-enrichment of CO2 and plasma a-ketoisocaproate (19±2 Mumollkg. hr-') increased at the 16 ,U/ml insulin level to 16±1 and 24±2 ,mol(kg. h)-', respectively (P < 0.05 for each), but did not increase at higher insulin levels. Alanine flux (206±13 Amol(kg-h)-Y) did not in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
118
2

Year Published

1987
1987
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 356 publications
(139 citation statements)
references
References 39 publications
12
118
2
Order By: Relevance
“…This previous study represented acute effects of insulin and may be more comparable to the studies performed in nondiabetic individuals (31,49,50), in which insulin was infused during a short period of time. In the current study, the diabetic patients received insulin treatment over an 11-day period, although they received an insulin intravenous infusion for several hours only.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…This previous study represented acute effects of insulin and may be more comparable to the studies performed in nondiabetic individuals (31,49,50), in which insulin was infused during a short period of time. In the current study, the diabetic patients received insulin treatment over an 11-day period, although they received an insulin intravenous infusion for several hours only.…”
Section: Discussionmentioning
confidence: 87%
“…The increased circulating insulin levels on 11 days of insulin treatment substantially reduced fasting glucose levels but had little impact on circulating amino acid concentrations and amino acid kinetics, reflecting protein turnover. Previous studies in nondiabetic people demonstrated that leucine carbon flux declined progressively in a dose-dependent manner on intravenous insulin infusion (31,49,50). However, these dose-dependent effects clearly showed that the near-maximal insulin effect was achieved when insulin was infused at a dose of 1 mU ⅐ kg Ϫ1 ⅐ min Ϫ1 (31).…”
Section: Discussionmentioning
confidence: 96%
“…In normal subjects, insulin suppresses proteolysis in a dosedependent manner (17,23). Castellino et al (9) and Tessari et al (17) found that insulin also suppresses leucine oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Castellino et al (9) and Tessari et al (17) found that insulin also suppresses leucine oxidation. Fukagawa et al (23), on the other hand, found variable effects of insulin on leucine oxidation (23). There are few studies documenting enhanced protein synthesis, one of which is that of Castellino et al (10) in CAPD patients.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10]20,21 In the pediatric population, one previous study measured the effects of insulin on protein metabolism in a cohort of 4 extremely low-birth-weight neonates. 22 The investigators showed a 20% reduction in protein breakdown, although this was associated with a corresponding decrease in protein synthetic rate.…”
Section: Discussionmentioning
confidence: 99%